Sacral and Anagogical Aspects of the “Marvellous” in Damascius. An Interpretation - Napoli, Valerio (Peitho. Examina Antiqua, 2018)
In the fragments of Damascius’ Vita Isidori one can observe a significant presence of the “marvellous.” In many cases, the marvellous seems to manifest a sacral and anagogical value in line with the philosophical and religious conceptions of late Neo-Platonism. A similar value of the marvellous can also be found in a passage of De Principiis (I, 14, 1–19), where Damascius hails the totally ineffable Principle as supremely marvellous, upon which he presents it as absolutely unknowable and expressible only in an aporetic way.